2010
DOI: 10.1021/ja101957c
|View full text |Cite
|
Sign up to set email alerts
|

Goldilocks Effect in Magnetic Bistability: Remote Substituent Modulation and Lattice Control of Photoinduced Valence Tautomerism and Light-Induced Thermal Hysteresis

Abstract: The thermal-induced and photoinduced valence tautomerism of a series of Co(dioxolene)(2)(4-X-py)(2) complexes (dioxolene = 3,5-di-tert-butylcatecholate or 3,5-di-tert-butylsemiquinonate; 4-X-py = 4-(X)pyridine, X = H (1), OMe (2), Me (3), CN (4), Br (5), NO(2) (6)) is described. The thermal valence tautomerism (ls-Co(III)(SQ)(Cat)(4-X-py)(2) <--> hs-Co(II)(SQ)(SQ)(4-X-py)(2)) is only observed for complexes 4, 5, and 6 where each is accompanied by a hysteresis loop of ca. 5 K. When a crystalline sample of 4-6 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 49 publications
3
85
0
1
Order By: Relevance
“…Benzene solvated crystals III are described by P1 space group, Z=2, and at 100 K. When compared with I and II, benzene solvated crystals present the shortest C ar -H…O i diox and similar C ar -H… ONO i hydrogen bonds lengths. They also present the shortest Co III -Co III distances between inlayer molecules linked by Car-H… O i diox and the longest Co III -Co III distances between Thus, as already pointed out before [6], VT in [Co III (SQ)(Cat)(4-NO 2 -py) 2 ] seems to be due to the intermolecular interactions between inlayer molecules, however the interconversion cooperativity seems to be related with the strength of the Car-H…O i diox interaction and with the correspondent Co-Coi separation.…”
Section: 2 and 3 Indicate Distances Between Cobalt Atoms In Molecusupporting
confidence: 80%
See 1 more Smart Citation
“…Benzene solvated crystals III are described by P1 space group, Z=2, and at 100 K. When compared with I and II, benzene solvated crystals present the shortest C ar -H…O i diox and similar C ar -H… ONO i hydrogen bonds lengths. They also present the shortest Co III -Co III distances between inlayer molecules linked by Car-H… O i diox and the longest Co III -Co III distances between Thus, as already pointed out before [6], VT in [Co III (SQ)(Cat)(4-NO 2 -py) 2 ] seems to be due to the intermolecular interactions between inlayer molecules, however the interconversion cooperativity seems to be related with the strength of the Car-H…O i diox interaction and with the correspondent Co-Coi separation.…”
Section: 2 and 3 Indicate Distances Between Cobalt Atoms In Molecusupporting
confidence: 80%
“…of complex [Co III (SQ)(Cat) (4-NO 2 -py) 2 ] (I), where py= pyridine, Cat = 3,5-di-tbutylcatecholate and SQ=3,5-ditbutylsemiquinonate, were first studied with respect to low spin (LS) to high spin (HS) thermo and photoinduced conversion. It was reported that I become HS-Co III at temperatures below 110 K with non cooperative LS-Co III n↔ HS-Co II tautometic interconversion [ 6 ]. Crystals of Co III (SQ)(Cat)(4-NO 2 -py) 2 ]/Toluene (II) and Co III (SQ)(Cat)(4-NO 2 -py) 2 ]/Benzene (III) have been prepared to investigate further the solvation effects on the interconversion properties.…”
Section: Crystalsmentioning
confidence: 99%
“…Below a certain blocking temperature, the photoexcited metastable state is maintained for very long times, which range from minutes till several days 22 . Thermal relaxation drives the system back into a ground state, which can be described by an Arrhenius law (τ: relaxation time, τ 0 : inverse attempt frequency, ∆: energy barrier, k B : Boltzmann constant, T : temperature).…”
Section: The Photomagnetic Processesmentioning
confidence: 99%
“…These compounds usually undergo the intramolecular ET between the coordinated metal center and the surrounding ligands, while this phenomenon is often accompanied by SCO behaviour of the metal ion, owing to the closely spaced d levels. The coordination compounds of the Co-catecholate/semiquinone families are known to display VT, and several examples have been reported, attracting considerable interest 7,10,21,22,[28][29][30][31][32] . Usually, the VT mechanisms implies the electron transfer from the ligands, leading to the interconversion between the lowspin Co III -catechole (Cat) and high-spin Co II -semiquinone (SQ) triggered by the presence of redox-active quinone ligands.…”
Section: Introductionmentioning
confidence: 99%
“…For example, with the drive to develop new devices, applications with single crystals are being explored. 18 However, the exploitation of molecule-based magnetic films may be more attractive for industrial fabrication, and devices based on metalphthalocyanines 19 and metal-͓TCNE: tetracyanoethylene͔ x ͑Ref. 20͒ are two examples of work in this direction.…”
Section: Introductionmentioning
confidence: 99%